LPI time‐based TMS against high‐sensitivity ESM. Issue 12 (1st December 2018) - Wang, Fei; Yu, Siwei; Shi, Chenguang; Sellathurai, Mathini
Abstract : Low probability of interception (LPI) time refers to a time during which a certain airborne radar system is tracking the target without being intercepted by a high‐sensitivity electronic support measurement (HSESM) on the target. LPI time is determined by the tracking process of the certain airborne radar system and the interception performance of an HSESM. This study proposes a track mission shifting (TMS) tactic of the distributed airborne radar system (DARS) or distributed airborne formation radar system (DAFRS) based on LPI time. First, this study defines a short‐time average interception probability of HSESM on frequency search mode. Then, with adaptive dwell time design and the maximum illumination interval algorithm based on predicted tracking error covariance matrix, this study proposes to take interactive multiple models Kalman filter to describe target tracking process and introduces binary hypothesis test of chi‐square and non‐central chi‐square distributions as target detection criterion during target tracking. Finally, with a partial prior knowledge of the opposed HSEMS on the target, this study proposes a TMS tactic model based on LPI time. Simulations show that LPI time is a significant reference value for DARS or DAFRS to turn over track mission against an opposed HSEMS.